Islam dan Modernitas: Analisa Dialog Kemanusiaan Perspektif Ali Hassan Zaidi - Irawan, Dedi (Himmah: Jurnal Kajian Islam Kontemporer, 2023)
This paper seeks to build a paradigm of social science approach that is relevant to Islam in the modern era. Modernization in Indonesia is currently towards the 5.0 era, which in the author's opinion is still essentially debatable. Meanwhile, the dialogue referred in this paper is an offer thats enable accepted by Muslim and non-Islamic communities. According to Ali Hassan Zaidi, dialogue has the universal quality, which can be used to appreciate each other even though distance separates both of them. In the first part, the author tries to explain the problems of modernity, as well as its influence on humans in general, and specifically on Islamic society. The second part, seeking the common ground between these problems with the theory of dialogue developed by Ali Hassan Zaidi. This type of research is qualitative-descriptive research using data collection methods, namely library research. By explaning these two problems, the author hopes to build a clear and more relevant paradigm. It is strengthened by the analysis of the sociological theory of dialogue developed by Ali Hassan Zaidi. Then with the conclusion that humanitarian dialogue is a solution to solve the social problems of Islamic society.